Pengaruh Waktu Dimulainya Pendinginan Selama Penetasan Terhadap Daya Tetas Telur Itik Persilangan Cihateup Alabio - Diniati, Diniati; Rukmiasih, Rukmiasih; Afnan, R. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
Duck eggs have lower hatchability because they have higher risk of embryo mortality due to a longer incubation than chicken eggs. This study was designed to obtain the proper of start cooling during artificial incubation to improve duck eggs hatchability and hatching weight. Eggs of cihateup alabio duck were obtained from Balai Penelitian Ternak (Balitnak) Ciawi. Eggs were collected weekly in 5 different times. Total egg collected was 419 eggs. Incubated eggs were sprayed and cooled for 0.25 h at room temperature for 2 times a day in setter period. This study used randomized block design and 3 treatments of starting cooling time of egg. Observed variables were egg weight, fertility, hatchability, embryo mortality and hatching weight. Cooling eggs at different times during the setter period did not affect to hatchability. Highest hatchability was obtained on Days 17. The start cooling significantly was affected the hatching weight.